Professional Competence of School Principals in Inclusive School Management: A Multi-Site Study in Sidoarjo, Indonesia - Sulistyowati, Lilik; Wardoyo, Dewie Tri Wijayanti; Karwanto, Karwanto (International Journal of Emerging Research and Review, 2026)
Objective: This study aims to describe and analyze the professional competence of school principals in managing inclusive schools through a multi-site study conducted at Buduran 2 Junior High School and Sidoarjo 6 Junior High School. Method: This research employed a descriptive qualitative design with a multi-site study approach. Data were collected through observations, in-depth interviews, and document analysis involving school principals, teachers, and other school stakeholders. The collected data were analyzed using qualitative data analysis procedures consisting of data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of school principals’ professional competence in inclusive education management. Results: The findings indicate that the professional competence of school principals is reflected in the internalization of an inclusive vision into strategic school policies and the establishment of specialized organizational structures to support services for students with special needs. The implementation includes the development of adaptive curricula through Individualized Education Programs (IEP), the application of differentiated learning strategies, and the provision of accessible infrastructure and psychosocial protection within the school environment. Novelty: This study highlights how professional leadership of school principals contributes to optimizing resource allocation, promoting academic equity through flexible assessment practices, and fostering a tolerant and accountable school ecosystem that supports inclusive education for all stakeholders.